Assessment of Thyroid Function in patients with β- Thalassaimia Major and Intermedia: A comparative Study - Abdulsalam Abdulla, Jamila; Kardagh Polus, Ranan (Diyala Journal of Medicine, 2019)
Background: Thalassemia is regarded as one of the most common hereditary disorders throughout the world. Endocrine disorders found among the commonest complications in thalassemic patients resulting from iron overload, especially thyroid. Objective: To investigate thyroid function and complications in patients with Beta thalassemia major and intermedia in Erbil city. Patients and Methods: This is prospective, cross sectional study (comparative study), the study was extended from September of 2018 till October of 2019 on 71 beta thalassemia major and 49 intermedia patients. The study was performed in the thalassemia center in Erbil city. Assay of thyroid hormones (thyroid function test) was performed by Roche Cobas E411 analyzer is fully automated immunoassay analyzer. Data were analyzed by using the statistical package for social science (SPSS) version22. Results: This retrospective cross sectional study was carried out on 196 subjects, from which 71 patients with thalasseamia major ,49 patients with thalassemia intermedia, and 78 case were control subject.in the thalassemia major 8 cases (11.3) % had hypothyroidism (TSH high and low T4) and 17 case (23.9) % were subclinical hypothyroidism (TSH high and T3 AND T4 normal), in intermedia group about 13 patients had subclinical hypothyroidism, in compared to control group about 3 (3.9) % subclinical. In both TI and TMthy, the proportion of hypothyroidism and subclinical hypothyroidism was significantly (P=0.037) higher in those 18 years old (38.9%) compared to the lower age group (20.8%). Conclusion: The thyroid function did not differ significantly by the other characteristics of the patients such as gender, consanguinity, chelation therapy, splenectomy status, organomegllay, BMI. Serum ferritin was found to be positively, but non-significantly correlated with T3 (r=0.78, p=0.398), negatively and significant statistically correlated with T4 (r=-0.231, p=0.011) and positively and significant statistically correlated with TSH (r=253, p=0.005). DOI:https://doi.org/10.26505/DJM.17024760626